ENVIRONMENTAL IMPACT OF CEMENT PRODUCTION ACTIVITIES IN BOOLANG REGENCY, MONGONDOW, NORTH SULAWESI - Ilham Akbar Mustafa; Hayati Sari Hasibuan; Ahyahudin Sodri (Universitas Medan Area, 2022)
The cement industry is a large industry that can have an impact on the surrounding environment. In the area of Boolang Regency, Mongondow, North Sulawesi, there is a foreign cement industry that has only been operating for about 2 years. Therefore, it is necessary to study the environmental impacts that have occurred around the cement industry. The objective of this study is to analyze the impact of the physical environment, especially water, on the production activities of the cement industry in Boolang Regency, Mongondow, North Sulawesi. The research method used was a laboratory test and the data were processed using STORET. The results showed that the water quality in the residents' wells was in very good condition, while the surface quality of the river water around the cement industry area could be categorized as lightly polluted.